Inequitable rent generation for renewable electricity producers in elcertifikatsystemet - Sun, Miao (2015)
Energy transition is a task faced by every country in order to combat climate change, therefore, the choice of renewable energy supporting policy is a crucial decision for politicians. In Europe, since Renewable Energy Directive was agreed in 2009, various policy schemes have been adopted in many countries, and Swedish Electricity Certificate System is one of them. Starting from 2003 until now, it has assisted Sweden to become the country with highest percentage of renewable electricity in total electricity generation among all the European member countries, and has included Norway from 2012 to create a joint market for electricity certificates between these two counties. However, the increase of renewable electricity production is only one part of the picture, while the other part is involved with concerns on the inequity among renewable electricity producers within the system. During more than tens years of operation, the systems has generated a large amount of benefits for a small share of renewable electricity producers, who have already been phased out of the system by the end of 2014, after obtaining excess percentage of payment by consumers. The technology-neutral nature of the policy scheme needs to be questioned, because it not only has created the equity issue in the past, but also indicates the same issue potentially in the future. The purpose of this study is to find out to what extent this inequity existed in the past, the impacts on different renewable electricity producers, and whether the inequity will continue to happen in the future. These conclusions will help us to see if the Swedish Electricity Certificate System is really a sustainable policy, or the one needs to be improved.